The Effect of Motivation, Competence and Organizational Commitment on Performance of Employees in Food and Beverage Manufacturing Company - Silvia Ekasari; Hartanto; Efin Shu; Yahya; Roy Setiawan (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study intends to examine and determine the impact of organizational commitment as an intervening variable on employee performance at one food and beverage company. In order to sample, permanent workers were given questionnaires using the Likert scale and one of the non-probability sampling approaches, known as saturation sampling. The SPSS application's route analysis is used in the data analysis process. There are two sub-structures in the research findings. In Sub-structure I, it is demonstrated that organizational commitment is significantly influenced by motivation, that it is not significantly influenced by human resource competence, and that it is significantly influenced concurrently by both motivation and human resource competence. According to Sub-Structure II, employee performance is significantly influenced by motivation, human resource competencies, organizational commitment, and employee performance. Additionally, employee performance is significantly influenced simultaneously by motivation, human resource competencies, and organizational commitment.